Dehydration of green mangoes (Mangifera Indica Linn. Var. Carabao) - Soriano, Helene May A.
A standard procedure for dehydration of mature, unripe green mangoes having a characteristic blend of sweet-sour-salty and spicy taste was developed. The optimum level of moisture content and amount of "kamchu" (a Chinese bark), salt and syrup level, and optimum drying time and temperature was determined. The effect of blanching as a method to eliminate starchiness was also evaluated. however, this was found to be ineffective. Results revealed that green mango strips was best added with 1.5% "kamchu" and 10% coarse dry salt, then allowed to stand overnight before soaking in 60'Bx syrup overnight. The salted-syruped green mango strips dried at 140'F for 4 hours or to a moisture level of 14% produced the most acceptable dehydrated green mangoes. The product had a "yellow" color, "firm" texture, "slight green mango flavor", "right blend" of sweet-salt combination, a "near ideal" "kamchu" flavor, and a general acceptability of "like moderately".